Epigenomics of embryogenesis in turbot - Aramburu, Oscar; Pardo, Belen G; Jimenez-Gonzalez, Ada; Blanco-Hortas, Andrés; Macqueen, Daniel; Bouza, Carmen; Martinez, Paulino

(untitled) (Genome Research, 2025)
Embryogenesis is the foundational step of ontogeny, where a complex organism emerges from a single totipotent cell. This process is orchestrated by changes in transcriptional regulation, influenced by chromatin accessibility and epigenetic modifications, enabling transcription factor accessibility. Epigenomic regulation of embryogenesis has been studied in model fish, but little attention has been paid to farmed fish - where relevant traits to aquaculture rely on early developmental processes. This study reports a regulatory atlas of turbot (Scophthalmus maximus) embryogenesis. 14,560 active genes were identified in the embryonic transcriptome with > 90% showing differential expression across consecutive stages. By integrating multi-histone ChIP-seq with ATAC-seq, we built a genome-wide chromatin state model, defining promoter and enhancer activity across stages. Diverse transcription factor binding motifs were detected within regulatory elements showing differential accessibility at distinct developmental stages. Strong shifts in chromatin accessibility across stages, notably during the transition from shield to early segmentation, suggest profound chromatin reorganization underpinning somitogenesis and early organogenesis. Regardless, most changes in chromatin accessibility did not affect promoters of differentially expressed genes, suggesting that their accessibility precedes gene transcription changes. Comparative analyses with zebrafish revealed a global transcriptomic correlation of single-copy orthologs at matched stages. While conserved expression dynamics were revealed for many orthologous Hox genes, notable cross-species differences were identified from pre-ZGA leading up to hatching. This multi-omics investigation provides a novel atlas of noncoding regulatory elements controlling turbot development, with key applications for flatfish biology and sustainable aquaculture.